Determination of Young’s modulus of Sb2S3 nanowires by in situ resonance and bending methods - Jasulaneca, Liga; Meija, Raimonds; Livshits, Alexander I.; Prikulis, Juris; Biswas, Subhajit; Holmes, Justin D.; Erts, Donats (Beilstein Journal of Nanotechnology, 2016)
In this study we address the mechanical properties of Sb2S3 nanowires and determine their Young’s modulus using in situ electric-field-induced mechanical resonance and static bending tests on individual Sb2S3 nanowires with cross-sectional areas ranging from 1.1·104 nm2 to 7.8·104 nm2. Mutually orthogonal resonances are observed and their origin explained by asymmetric cross section of nanowires. The results obtained from the two methods are consistent and show that nanowires exhibit Young’s moduli comparable to the value for macroscopic material. An increasing trend of measured values of Young’s modulus is observed for smaller thickness samples.
Keywords: antimony sulfide; in situ; mechanical properties; nanowires; Young’s modulus